Revisiting learning in higher education—Framing notions redefined through an ecological perspective - Damsa, Crina I.; Jornet, Alfredo (Frontline Learning Research, 2017)
In this contribution, we employ an ecological approach as a resourceful means of revisiting the notion of learning in the knowledge society in general and in higher education in particular. Learning is re-conceptualised as a process entailing mutually constitutive, epistemic, social and affective relations in which knowledge, identity and agency become collective achievements of ecosystems. This process entails a trans-contextual and multimodal endeavour, through which both learners and their social and material environments change. Throughout the paper, we discuss implications of an ecological approach to framing notions central to current educational research, namely (a) knowledge co-construction and epistemic agency, (b) the role of (material) knowledge resources in the learning process and (c) the trans-contextuality that characterises learning in today’s knowledge society. We conclude by discussing prospects that an ecological perspective offer to higher education research and practice. The insights emerging from this re-conceptualisation imply changes in the ways we analytically account for and enhance the transformative potential of education. They also indicate a necessity for further advancing our understanding of learners’ ways of assembling the epistemic space necessary to engage in meaningful learning, their agency and authoritative positioning in this process, and their relationship with the (social, material) environment.